CONDITIONAL SENTENCES IN JAPANESE AND ENGLISH: A CONTRASTIVE STUDY - Diana Kartika; Irma Irma (Leksema: Jurnal Bahasa dan Sastra, 2021)
This research explores the differences in presupposition patterns in terms of conditions and usage similarities between Japanese and English. This paper uses comparative analysis, and the results show that there are some similarities and differences between Japanese and English conditional sentences. First, conditional clauses exist in both conditional Japanese and English sentences and these clauses have two parts: the â€˜if-clauseâ€™ as the situation and the â€˜main-clauseâ€™ as the result. Second, conditional sentences in both languages have similarities in that they express the possibilities and suppositions of the speakers. Third, conditional sentences in Japanese comprise ã¨ (-to), ã° (-ba), ãªã‚‰ (-nara), and ãŸã‚‰ (-tara) sentences. Fourth, there are three types of conditional sentences in English, namely the conditional that is true in the present/future tense, untrue in the present/future tense, and untrue in the past tense. Fifth, the conditional sentence in Japanese using -to, -ba, -tara, and -nara can all be used inherently in the predicate of the clause.